Pola Siklus Haid dan Peran Mekanisme Koping pada Mahasiswa Kedokteran dengan Dismenore: Sebuah Studi Observasional - Ika Ulfi Khabibah; Zulkhah Noor (Majalah Kedokteran Indonesia, 2025)
Introduction: More than 50% of women worldwide experience dysmenorrhea, and its often worsening with irregular menstrual cycles. Women adopt both adaptive and maladaptive coping mechanisms to manage pain. This study examines the relationship between menstrual cycle irregularities, dysmenorrhea severity, and coping mechanisms. Method: This a cross-sectional study involving medical students in Faculty of Medicine and Health Sciences, Universitas Muhammadiyah Yogyakarta (UMY), from September to November 2022. The inclusion criteria aged 18 to 23 years, physically healthy with no history of reproductive health issues, possessing a normal body mass index (BMI), and being non-smokers. Data on menstrual cycles pattern (normal, poly-, or oligomenorrhea), dysmenorrhea severity, and coping mechanisms were collected through online validated-questionnaires and analyzed using the Chi-Square test. Results: Among 174 subjects, the majority experienced moderate dysmenorrhea (67.8%) and had a normal menstrual cycle (81.6%). A total of 93.6% employed adaptive coping mechanisms. This study found a significant association between the menstrual cycle and the severity of dysmenorrhea (p=0.031), as well as the effectiveness of adaptive coping in reducing dysmenorrhea severity (p=0.0001). Conclusion: The length of the menstrual cycle is associated with dysmenorrhea severity, while adaptive coping mechanism may alleviates its intensity.